A Student's Dictionary Of Psychology And Neuroscience - Hayes, Nicky; Stratton, Peter (2017)
An essential reference work for any undergraduate psychology student or those studying psychology for the first time, including related disciplines such as health care and social sciences. Packed with easy to understand definitions and helpful diagrams, the new edition has been expanded to include the key concepts within the growing field of neuroscience, as well as greater coverage of positive psychology. Also including a list of key references in the field, and a guide to writing essays and referencing your work, this is the perfect accompaniment for any student newly encountering this fascinating subject, or professionals wanting to familiarise themselves with key terms and ideas.
Previous edition: published as A student's dictionary of psychology. London: Hodder Education, 2012.
Includes bibliographical references.
Keywords: Psychology -- Dictionaries; Psychology